Monitoring Budget Allocation on Performance of Socio-Economic Empowerment Projects: A case of Women and Law in Southern Africa Research and Education Trust Project - Itumeleng G. Letsolo; Nderitu B. Wanjiru; Peter Gaiku (European Scientific Journal, ESJ, 2022)
This study seeks to investigate the influence of the monitoring and evaluation (M&E) budget allocation on the performance of socio-economic empowerment projects. The overarching theoretical framework is the resource-based view theory. The study adopted quantitative approaches to gather an in-depth understanding of the research variables and to allow a researcher to make informed recommendations using both words and numbers. The research site for the study is Women and Law Southern Africa -Lesotho. The target population of 68 project team members. A census method was adopted and the researcher used questionnaires to collect data from 68 respondents. To test reliability the research tools were piloted before actual data collection. Further, Cronbach’s alpha coefficient was used to estimate instrument reliability using the pilot responses and it returned 0.818 which was fairly high. Content and face validity were adopted to test instrument validity. Proper authorizations were secured from relevant bodies to conduct the study and SPSS Version 23 data analysis software was deployed to analyze the collected data. The researcher further analyzed the data through descriptive analysis with means and standard deviation to measure central tendencies and dispersion of the data. The general findings of the study indicated that the response was higher than a composite mean of 4.37 with a standard deviation of 0.745, implying that the study objective; of monitoring budget allocation positively influences the performance of the socio-economic empowerment project. Findings implied that the team should, as part of best practice, maintain the M&E budget separately and promote transparency by issuing the M&E budget performance reports. The study made recommendations for improving M&E budgeting. The study suggests comparative studies to be conducted on other socio-economic empowerment projects and the usage of hybrid approaches of qualitative and quantitative approaches to gather as much information as possible. The study findings conformed to the principles of resource-based view theory that advocates for adequate allocation of resources to enable the monitoring and evaluation team to execute the activities according to plan.